Severe Hypertriglyceridemia in Pregnancy A Case Report - Ivy, Rokshana; Jahan, Rawshan Hosne; Ara, Anjuman (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
We report a case of a 33 years primigravida who had regular antenatal check up and her pregnancy was uneventful till 30 weeks of pregnancy when she developed hypertension and her blood pressure was 150/90 mm of Hg. At that time urinary protein was trace and she was treated conservatively. At 33 weeks of pregnancy, her blood pressure raised to 160/105 mm of Hg along with mild proteinuria. Serum creatinine and uric acid levels were within normal range. Ultrasonography revealed 32 weeks pregnancy with fetal weight 1800 gm and AFI 7 cm. The patient was treated conservatively. At 36 weeks of pregnancy, the patient perceived less fetal movement and Biophysical profile was found 6. Emergency caesarean section was done. During operation, blood was found pinkish in colour and after keeping the placenta on kidney dish, milky fluid was accumulated around the placenta. Urgently lipid profile of the patient was done and the report revealed high Triglyceride (3012mg/dl) and cholesterol levels (348 mg/dl). The postoperative period was uneventful and she was treated with injection Heparin in the immediate postoperative period followed by low fat diet and lipid lowering agents. Bangladesh J Obstet Gynaecol, 2014; Vol. 29(1) : 43-45